1971
DOI: 10.1136/bmj.3.5768.228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Non-puerperal Galactorrhoea with an Ergot Alkaloid

Abstract: SummaryThree patients suffering from non-puerperal galactorrhoea over periods ranging from two months to six years were treated with an ergot alkaloid, 2-Br-alphaergocryptine (CB 154). In all three cases the galactorrhoea was terminated. The apparent prolactin antagonism exhibited by this compound is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 2 publications
2
34
0
Order By: Relevance
“…This has been consistently demonstrated in all species tested: e.g., mice (Yanai and Nagasawa, 1970;Sinha et al, 1974), rats Gala and Boss, 1975), domestic animals (Karg, Schams and Reinhardt, 1972), and man (Lutterbeck et al, 1971;Rozeneweig et al, 1973). The ergot can also suppress prolactin secretion in rodents treated with oestrogen Gala and Boss, 1975), which is well known to enhance prolactin secretion (Meites and Nicoll, 1966).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This has been consistently demonstrated in all species tested: e.g., mice (Yanai and Nagasawa, 1970;Sinha et al, 1974), rats Gala and Boss, 1975), domestic animals (Karg, Schams and Reinhardt, 1972), and man (Lutterbeck et al, 1971;Rozeneweig et al, 1973). The ergot can also suppress prolactin secretion in rodents treated with oestrogen Gala and Boss, 1975), which is well known to enhance prolactin secretion (Meites and Nicoll, 1966).…”
Section: Discussionmentioning
confidence: 79%
“…It would be of great interest to determine whether or not concurrent treatment of these women with drugs such as CB-154 would suppress or prevent these dysplastic epithelial breast changes. CB-154 has already been used extensively and successfully as a prolactin suppressor in women to halt puerperal and non-puerperal lactation (del Brun et al, 1973;Lutterbeck et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…In accord, approximately 3 times the level of prolactin was found in the serum ofthe grafted rats in this study when compared with the controls. More recently, it has been shown that the administration of a number of ergot alkaloids or ergoline derivatives can induce hypoprolactinaemia in rats Clemens et al, 1974) as well as in man (Lutterbeck et al, 1971). CB-154 appears to be one of the most effective prolactin suppressors currently available (Brooks and Welsch, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Ergot alkaloids are known to inhibit prolactin secretion primarily through the direct action to the pituitary (Lu et al, 1971), but also indirectly through the increase of hypothalamic prolactin inhibiting factor activity (Wuttke et al, 1971). Clinical application of CB-154 has proved effective to suppress puerperal (Del Pozo et al, 1972;Brun del Re et al, 1973), and nonpuerperal (Lutterbeck et al, 1971;Copinshi et al, 1971Copinshi et al, /1972Del Pozo et al, 19729 Varga et al, 1973) lactation.…”
Section: Discussionmentioning
confidence: 99%
“…2-Br-ƒ¿-ergocryptine (Fluckiger and Wagner, 1968;Yanai and Nagasawa, 1970;Billeter and Fluckiger, 1971;Fluckiger et al, 1972), in human pituitary tissue cultures (Pasteels et al, 1971), and in clinical trials (Lutterbeck et al, 1971;Besser et al, 1972;, but not of growth hormone (GH) Nagasawa, 1970 andMacLeod and Lehmeyer, 1972 GH as well as prolectin. The multihormonal activities of pituitary tumor cells were also described in the human being (Zimmerman et al, 1974), suggesting that CB-154 might be useful for the treatment of acromegalic patient with galactorrhea.…”
mentioning
confidence: 99%